Westernisation, Rationalisation, Amalgamation: Party Politics in Intercivilisational Encounters - Simral, Vit (Richtmann Publishing, 2012)
During the last two decades, the perceived rise of Asian powers has led to a gradual shift in the academic view of thedevelopment of humanity from one of Westernisation to one of globalisation. Concurrently, students of civilisations re-started afresh theirongoing debate how and to what extent different cultures in the world influence each other. Many political scientists believe that there iseither already an end to inter-civilisational conflicts and the victory of the West is complete, or that there are intrinsic, insuperabledifferences between world cultures; scholars of historical sociology, on the other hand, advocate a less radical, but perhaps morecompelling model: one of inter-civilisational encounters, where civilisations in the course of history managed to adopt an idea comingfrom outside their cultural sphere, adapt it and assimilate it into their own ideology. From a historical-sociological perspective, drawing onthe Weberian strand of the current debate, the presented paper focuses on the transformation of political partisanship in ancient,medieval, early modern and modern civilisations. It proposes that general characteristics of party systems may be found in predemocraticperiods from which they developed into modern democratic politics. Moreover, it wants to assess the impact that non-Western societies have had in the 20th century on the global image of a political party. In conclusion, it argues for a notion ofamalgamation of ideas in today’s political partisanship in place of a one-sided theory of Westernisation.